Aluminum foil and method for producing same
By forming a specific concave-shaped concave and convex surface on the surface of the aluminum foil, the reflection characteristics of ultraviolet rays are optimized, and the problem that existing aluminum foil cannot achieve uniform sterilization in the space to be sterilized is solved, and its white reflection characteristics under visible light are improved.
Patent Information
- Application Number
- CN202380060536.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-10-13
- Filing Date
- 2023-06-27
- Publication Date
- 2025-03-18
AI Technical Summary
The intensity of the existing aluminum foil reflects ultraviolet rays at specific angles is high, resulting in the inability to achieve uniform sterilization in the space to be sterilized.
By forming a concave-shaped concave-convex surface on the surface of the aluminum foil, the area ratio of the second phase particles, the arithmetic average curvature of the convex portions and the apex density of the concave portions are controlled to optimize the reflection characteristics of the ultraviolet rays.
The effect of uniform sterilization in the space to be sterilized is achieved, and the white reflection characteristics of aluminum foil under visible light are improved.
Smart Images

Figure CN119654443A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an aluminum foil and a method for making the same. Background Art
[0002] Deep ultraviolet lamps that utilize the sterilization effect of ultraviolet rays are used to remove viruses and various pathogens from air, objects, water, etc. Aluminum is the only metal material with high reflectivity for ultraviolet rays in the wavelength range of 250nm to 400nm. Among aluminum components, aluminum foil, which is lightweight and highly processable, is particularly suitable as an ultraviolet reflective material.
[0003] International Publication No. 2017 / 158989 (Patent Document 1) discloses an aluminum foil for an ultraviolet reflective material having specific surface properties.
[0004] In the aluminum foil for ultraviolet reflective material described in Patent Document 1, the area ratio of aluminum particles and crystals present on the foil surface and the smoothness of the foil surface are controlled, the regular reflection component of ultraviolet rays is increased, and a high focusing effect can be obtained. In the aluminum foil described in Patent Document 1, the total reflectance measured by an integrating sphere in the wavelength range of 250 to 400 nm is more than 80%, but the regular reflectance is also more than 70%. Regular reflection refers to the reflection of the incident angle and the reflection angle being equal, and the reflected light is a parallel light.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: International Publication No. 2017 / 158989 Summary of the invention
[0008] Problems to be solved by the invention
[0009] The aluminum foil described in Patent Document 1 is not suitable as a reflector for uniformly sterilizing a space to be sterilized, because the intensity of ultraviolet rays reflected at a specific angle is significantly higher than the intensity of ultraviolet rays reflected at angles other than the specific angle.
[0010] The main object of the present invention is to provide an aluminum foil and a method for manufacturing the same, which is suitable for a reflective plate that is used to sterilize a space uniformly.
[0011] Means of solving the problem
[0012] The aluminum foil of the present invention has a concavoconvex surface on which concavoconvexities in a concavoconvex shape are formed, the area ratio of the second phase particles existing in a predetermined area of the concavoconvex surface is 0.10% or less, the arithmetic mean curvature Spc (1 / mm) of the convex portion of the concavoconvex shape is 3700 or more and 10000 or less, and the vertex density (1 / mm) of the concave portion of the concavoconvex shape is2 ) is greater than 1,600,000 and less than 4,500,000.
[0013] The aluminum foil preferably contains aluminum, 0.04 mass % to 0.11 mass % of iron, and 0.50 mass % to 1.20 mass % of manganese.
[0014] It is preferable that the thickness of the aluminum foil is 4 μm or more and 300 μm or less.
[0015] In the above aluminum foil, it is preferred that the arithmetic mean roughness (Ra) of the concavo-convex surface is larger than 20 nm.
[0016] The method for manufacturing an aluminum foil of the present invention comprises the following steps: a step of preparing an aluminum foil containing aluminum, 0.04 mass % or more and 0.11 mass % or less of iron, and 0.50 mass % or more and 1.20 mass % or less of manganese; and a step of forming concave-shaped projections and depressions on at least a portion of the surface by exposing the surface of the aluminum foil to an alkaline aqueous solution.
[0017] Effects of the Invention
[0018] According to the present invention, it is possible to provide an aluminum foil and a method for manufacturing the same, which are suitable for a reflective plate that uniformly sterilizes a space to be sterilized. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is a schematic cross-sectional view showing the aluminum foil according to the present embodiment.
[0020] Figure 2 This is a partially enlarged cross-sectional view for explaining dimple-shaped concavities and convexities formed on at least a portion of the surface of the aluminum foil according to the present embodiment.
[0021] Figure 3 This is a partially enlarged plan view for explaining dimple-shaped concavities and convexities formed on at least a portion of the surface of the aluminum foil according to the present embodiment.
[0022] Figure 4 1 is a flowchart showing a method for producing the aluminum member for a visible light reflector according to the present embodiment. DETAILED DESCRIPTION
[0023] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings. In the following drawings, the same or corresponding parts are denoted by the same reference numerals and will not be described repeatedly.
[0024] In this specification, the term "aluminum foil" is used to mean not only pure aluminum foil but also aluminum alloy foil.
[0025] <Composition of aluminum foil>
[0026] like Figure 1 As shown, the aluminum foil 1 of this embodiment has a first surface 1A and a second surface 1B as surfaces facing outward. The second surface 1B faces the direction opposite to the first surface 1A. At least a portion of the first surface 1A and the second surface 1B is a concave-convex surface having concave-convex shapes. For example, the entire first surface 1A may be a concave-convex surface. The entire second surface 1B may not be a concave-convex surface.
[0027] (1) Composition of concave and convex surfaces
[0028] Figure 2 and Figure 3 It is a partially enlarged cross-sectional view or a partially enlarged plan view for illustrating the concavo-convex surface on which dimple-shaped concavo-convexities are formed in the aluminum foil 1 .
[0029] like Figure 2 and Figure 3 As shown in FIG. 1 , the dimple-shaped concavo-convex is formed by a plurality of dimples formed by filling at least a portion of the first surface 1A without gaps. In this specification, the bottom surface portion including the valley bottom point (deepest portion) of each of the plurality of dimples is referred to as a dimple-shaped concave portion. In this specification, the boundary portion between two adjacent dimples among the plurality of dimples is referred to as a dimple-shaped convex portion. Figure 2 The solid line in the frame of illustrates the ridgeline of the convex part of the dimple shape (the boundary part between two adjacent dimples among the plurality of dimples). The concave part of the dimple shape is a part located on the valley bottom side compared to the reference plane that can be set when observing the above-mentioned concavoconvexity on the surface of the aluminum foil 1 using a laser microscope according to the method described later. The convex part of the dimple shape is a part protruding to the opposite side of the valley bottom relative to the above-mentioned reference plane.
[0030] like Figure 2 and Figure 3 As shown, the shapes and sizes of the plurality of dimples, as well as the connection relationship between the adjacent plurality of dimples, are, for example, various, but not the same.
[0031] (A) Arithmetic mean curvature Spc of the convex portion of the dimple shape
[0032] In the aluminum foil 1 , the arithmetic mean curvature Spc (unit: 1 / mm) of the dimple-shaped convex portions is 3700 to 10000. Preferably, the arithmetic mean curvature Spc (unit: 1 / mm) of the dimple-shaped convex portions is 3750 to 9900.
[0033] The arithmetic mean curvature Spc of the convex portion of the dimple shape is the arithmetic mean curvature Spc of the peak point of the convex portion measured from the three-dimensional shape observed using a confocal laser microscope by a measurement method that conforms to the International Organization for Standardization standard ISO25178. The arithmetic mean curvature Spc of the convex portion of the dimple shape can be measured, for example, by using a laser microscope VK-X3000 manufactured by Keyence Corporation to obtain three-dimensional shape data of the first surface 1A of the aluminum foil 1 in a rectangular field of view of 95.257 μm×71.419 μm, and using the data to measure using a multi-file analysis application attached to the microscope.
[0034] The present inventors have confirmed that when the arithmetic mean curvature Spc (unit: 1 / mm) of the dimple-shaped convex portions of the first surface 1A of the aluminum foil 1 is 3700 or more and 10000 or less, the total reflectance using an integrating sphere is 80% or more but the regular reflectance is suppressed to less than 4%.
[0035] The inventors of the present invention have confirmed that if the arithmetic mean curvature Spc (unit: 1 / mm) of the above-mentioned convex portion of the concave shape of the first surface 1A of the aluminum foil 1 is less than 3700, the regular reflectivity of the ultraviolet rays incident on the first surface 1A cannot be sufficiently reduced. It can be considered that if the arithmetic mean curvature Spc (unit: 1 / mm) of the above-mentioned convex portion of the concave shape is less than 3700, the angle range of diffuse reflection of the ultraviolet rays incident on the first surface 1A is narrowed, so the intensity of the ultraviolet rays (hereinafter, it may also be expressed as regular reflection component) reflected at a specific angle is not sufficiently reduced, and the intensity of the ultraviolet rays (hereinafter, it may also be expressed as diffuse reflection component) diffusely reflected at angles other than it cannot be sufficiently increased. In addition, the inventors of the present invention have confirmed that the arithmetic mean curvature Spc (unit: 1 / mm) of the surface of the aluminum foil described in the above-mentioned patent document 1 without forming the concave and convex of the concave shape is 563, and the total reflectivity is 86.6%, and the regular reflectivity is 72.1% (refer to Comparative Example 14 described later). It is considered that when the arithmetic mean curvature Spc is reduced to this extent, the above tendency is further strengthened, and the intensity of the diffuse reflection component is significantly lower than the intensity of the regular reflection component.
[0036] On the other hand, the present inventors have confirmed that if the arithmetic mean curvature Spc (unit: 1 / mm) of the above-mentioned convex portion of the concave shape of the first surface 1A of the aluminum foil 1 is greater than 10000, the total reflectivity of the ultraviolet rays incident on the first surface 1A is reduced to less than 80%. Although the reason is uncertain, the present inventors believe that this is because if the arithmetic mean curvature Spc (unit: 1 / mm) of the above-mentioned convex portion of the concave shape is greater than 10000, the angle range of diffuse reflection of the ultraviolet rays incident on the first surface 1A is too large, and a part of the ultraviolet rays diffusely reflected on the wall surface of the convex portion or concave portion of the concave shape is diffusely reflected again on the opposite wall surface, resulting in an increase in the amount of ultraviolet rays reflected multiple times in the first surface 1A and a decrease in the amount of ultraviolet rays emitted to the outside.
[0037] (B) Vertex density of the above-mentioned concave portion of the dimple shape
[0038] In the aluminum foil 1, the vertex density of the dimple-shaped concave portions (unit: 1 / mm 2 ) is 1,600,000 or more and 4,500,000 or less. The vertex density of the above-mentioned concave portion of the dimple shape (unit: 1 / mm 2 ) is greater than 1510000 and less than 4650000. The vertex density (unit: 1 / mm2) of the above-mentioned concave portion of the preferred dimple shape is 2 ) is 1610000 or more and 4000000 or less. More preferably, the vertex density (unit: 1 / mm 2 ) is greater than 1,620,000 and less than 3,500,000.
[0039] The vertex density of the above-mentioned concave portions of the dimple shape is the density of the valley bottom points of each of the plurality of dimples measured from the three-dimensional shape observed using a confocal laser microscope using a measurement method that conforms to the International Organization for Standardization standard ISO25178. The vertex density of the above-mentioned concave portions of the dimple shape is obtained, for example, by using a laser microscope VK-X3000 manufactured by KEYENCE Corporation to obtain three-dimensional shape data of the first surface 1A of the aluminum foil 1 in a rectangular field of view of 95.257μm×71.419μm, inverting the data in the height direction relative to the reference plane, and measuring the inverted data using a multi-file analysis application attached to the microscope as the vertex density Spd (unit: 1 / mm) of the mountain specified in the International Organization for Standardization standard ISO25178. 2 ). The reference plane of the three-dimensional shape data is set as an average plane representing the concavities and convexities of the three-dimensional shape data. As described above, the concave portion of the dimple shape is a portion located on the valley bottom side relative to the reference plane. In the above measurement method, by reversing the three-dimensional shape data in the height direction relative to the reference plane, the valley bottom point of each dimple can be measured and obtained as a peak point.
[0040] The present inventors have confirmed that in the aluminum foil 1, if the vertex density (unit: 1 / mm 2 ) is greater than 1,600,000 and less than 4,500,000, then although the total reflectance using the integrating sphere is greater than 80%, the regular reflectance can also be suppressed to less than 4%.
[0041] The present inventors have confirmed that in the aluminum foil 1, if the vertex density (unit: 1 / mm 2 ) is less than 1510000, it is difficult to suppress the regular reflectance to less than 4%. It can be considered that if the vertex density of the above-mentioned concave portion of the dimple shape (unit: 1 / mm 2 ) is less than 1510000, the number of dimples is small, so the diffuse reflection component becomes less, or the plane size of each dimple is large, so the angle range of ultraviolet diffuse reflection becomes narrower.
[0042] The present inventors have confirmed that in the aluminum foil 1, if the vertex density (unit: 1 / mm 2 ) is greater than 4650000, the total reflectivity of the ultraviolet rays incident on the first surface 1A is reduced to less than 80%. As for the reason, the inventors of the present invention believe that if the vertex density (unit: 1 / mm 2 ) is greater than 4650000, the planar size of each dimple is too small, and a part of the ultraviolet rays diffusely reflected on the wall of the convex or concave portion of the dimple shape is diffusely reflected again on the opposite wall, resulting in an increase in the amount of ultraviolet rays reflected multiple times within the first surface 1A and a decrease in the amount of ultraviolet rays emitted to the outside.
[0043] (C) Area ratio of the second phase particles existing on the above-mentioned concavoconvex surface
[0044] In the aluminum foil 1, the area ratio of the second phase particles existing in the predetermined area of the above-mentioned concave-convex surface is 0.10% or less. The so-called second phase particles mean various intermetallic compounds such as Al-Fe system, Al-Fe-Mn system, Al-Mg-Si system, Al-Mn system, Al-Fe-Si system, Al-Mn-Fe-Si system, or alloy additive elements precipitated in the aluminum matrix. The second phase particles existing in the above-mentioned concave-convex surface come from the second phase particles existing in the aluminum foil before the above-mentioned concave-convex surface is formed, and the aluminum foil is not removed but remains when the concave-convex surface forming method described later is implemented. In this specification, the so-called predetermined area of the concave-convex surface of the aluminum foil 1 means the field of view where the second phase particles can be observed visually or under a microscope. The predetermined area of the concave-convex surface is, for example, 1188.49μm 2 A plurality of dimples are formed without gaps in a predetermined area of the concave-convex surface of the aluminum foil 1.
[0045] The area ratio of the second phase particles was measured as follows: 2 The backscattered electron image of a rectangular field of view (39.59 μm × 30.02 μm) is binarized, and the total area of the extracted second-phase particles is divided by the area of the field of view. The area ratio of the second-phase particles can be measured, for example, by using the image processing software WinRoof2021 manufactured by Mitani Shoji Co., Ltd. for a 1188.49 μm image taken by JSM-7200F manufactured by JEOL Ltd. 2 The backscattered electron image of a rectangular field of view (39.59 μm × 30.02 μm) was binarized and measured by dividing the total area of the extracted second phase particles by the area of the field of view.
[0046] The reflectivity of ultraviolet rays incident on the surface of the second phase particles existing in the above-mentioned concave-convex surface of the aluminum foil 1 is lower than the reflectivity of electromagnetic waves incident on the above-mentioned concave-convex surface of the aluminum foil 1 itself. The present inventors have confirmed that if the area ratio of the second phase particles existing in the predetermined area of the above-mentioned concave-convex surface of the aluminum foil 1 is less than 0.10%, the total reflectivity of ultraviolet rays incident on the concave-convex surface is more than 80%. In addition, the present inventors have confirmed that even if the area ratio of the second phase particles existing in the predetermined area of the above-mentioned concave-convex surface of the aluminum foil 1 is more than 0.02%, the total reflectivity of ultraviolet rays incident on the concave-convex surface is more than 80%. In addition, the present inventors have also confirmed that even if the area ratio of the second phase particles existing in the predetermined area of the above-mentioned concave-convex surface of the aluminum foil 1 is more than 0.00% and less than 0.02%, the total reflectivity of ultraviolet rays incident on the concave-convex surface is more than 80%.
[0047] On the other hand, the present inventors have confirmed that when the area ratio of the second phase particles present in the predetermined region of the concavo-convex surface of the aluminum foil 1 is 1.97% or more, the total reflectance of ultraviolet rays with a wavelength of 250 to 400 nm decreases to less than 80%.
[0048] (D) Arithmetic mean roughness Ra of concave and convex surface
[0049] The arithmetic average roughness Ra of the concavo-convex surface of the aluminum foil 1 is greater than 20 nm. The arithmetic average roughness Ra of the concavo-convex surface can be measured by a measurement method according to ISO4287 (1997 edition). The arithmetic average roughness Ra of the concavo-convex surface can be greater than 100 nm. The arithmetic average roughness Ra of the concavo-convex surface can also be less than 660 nm.
[0050] (2) Method for forming the concave and convex surface
[0051] The above-mentioned concavoconvex surface of the aluminum foil 1 can be formed by applying such a treatment to the surface of the aluminum foil prepared by any method. For example, the above-mentioned concavoconvex surface can be formed by exposing the surface of the aluminum foil to an alkaline aqueous solution (immersion or contact). The alkaline aqueous solution is not particularly limited, but is preferably an aqueous sodium hydroxide solution. In this case, the time for immersing the aluminum foil in the sodium hydroxide aqueous solution to form the above-mentioned concavoconvex surface is longer than the time for immersing the aluminum foil in the sodium hydroxide aqueous solution to clean the surface of the aluminum foil. The time for immersing the aluminum foil in the sodium hydroxide aqueous solution to form the above-mentioned concavoconvex surface is, for example, more than 5 minutes. The above-mentioned concavoconvex surface can also be formed by applying electrolytic grinding, cutting, surface transfer (for example, rolling, roller pressing, or embossing) and the like to the surface of the aluminum foil. In addition, the above-mentioned concavoconvex surface can also be formed by combining the above-mentioned two or more treatment methods.
[0052] (3) Composition of aluminum foil
[0053] The aluminum foil 1 contains aluminum (Al) and inevitable impurities. Preferably, the aluminum foil 1 further contains 0.04 mass % to 0.11 mass % of iron (Fe) and 0.50 mass % to 1.20 mass % of manganese (Mn). In such an aluminum foil 1, the above-mentioned uneven surface can be easily formed using an alkaline aqueous solution.
[0054] If the aluminum foil 1 contains iron (Fe) of 0.04 mass % or more and 0.11 mass % or less and manganese (Mn) of 0.50 mass % or more and 1.20 mass % or less, the above-mentioned concave-convex surface can be efficiently formed by exposing the surface of the aluminum foil 1 to an alkaline aqueous solution. When the aluminum foil 1 contains Fe and Mn, second phase particles such as Al-Fe-Mn system and Al-Mn system are crystallized or precipitated. The second phase particles containing Mn are easily removed from the surface of the aluminum foil during the process of exposing the surface of the aluminum foil to an alkaline aqueous solution and dissolving the aluminum matrix phase. In addition, the potential difference between the second phase particles containing Fe and the aluminum matrix phase is greater than the potential difference between the second phase particles not containing Fe and the aluminum matrix phase. Therefore, the second phase particles containing Fe will dissolve more efficiently in the alkaline aqueous solution than the second phase particles not containing Fe. Therefore, by exposing the surface of the aluminum foil containing 0.04 mass % or more and 0.11 mass % or less of Fe and 0.50 mass % or more and 1.20 mass % or less of Mn to an alkaline aqueous solution, the above-mentioned concavoconvex surface with an area ratio of the second phase particles of 0.10% or less can be easily formed. In addition, if the aluminum foil 1 contains both Fe and Mn as described above, the growth of the crystal grains is suppressed during annealing, etc., compared with the case where the aluminum foil 1 does not contain both Fe and Mn, so the crystal grains in the aluminum foil 1 can be refined.
[0055] It is considered that when the Fe content is less than 0.04 mass%, even when the surface of the aluminum foil 1 is exposed to an alkaline aqueous solution, the dissolution proceeds slowly, and the unevenness of the concave-convex surface caused by the dissolution increases, and the diffuse reflection component decreases. In other words, when the surface of the aluminum foil 1 with an Fe content of less than 0.04 mass% is exposed to an alkaline aqueous solution and the concave-convex surface is to be formed, the arithmetic mean curvature Spc (unit: 1 / mm) of the convex portion of the dimple shape is less than 3700, and the regular reflectivity may become high.
[0056] When the Fe content is more than 0.11 mass %, after the surface of the aluminum foil 1 is exposed to an alkaline aqueous solution to form the above-mentioned uneven surface, the area ratio of the second phase particles existing (remaining) on the above-mentioned uneven surface is greatly increased than 0.10%, and the total reflectance may be lower than 80%.
[0057] When the Mn content is less than 0.50 mass %, after the surface of the aluminum foil 1 is exposed to an alkaline aqueous solution to form the above-mentioned concave-convex surface, second phase particles with a small amount of Mn or no Mn remain on the above-mentioned concave-convex surface, the area ratio of the second phase particles is higher than 0.10%, and the total reflectance may be reduced to less than 80%.
[0058] When the Mn content is more than 1.20 mass %, the aluminum foil contains a large amount of Al-Fe-Mn crystals that are finer than Al-Fe crystals, and when the surface is exposed to an alkaline aqueous solution, a large amount of fine Al-Fe-Mn crystals are removed from the surface, and fine dimples are easily formed densely, and the arithmetic mean curvature Spc (unit: 1 / mm) of the convex portion of the dimple shape is greater than 10000, and the vertex density (unit: 1 / mm) of the concave portion of the dimple shape is greater than 10000. 2 ) is greater than 4500000, and the total reflectivity may be less than 80%.
[0059] More preferably, in the aluminum foil 1, the content of silicon (Si) is greater than 0.001% and less than 0.3% by mass. Si has a large solid solubility in Al and is difficult to form crystals. Therefore, if the content in the aluminum foil is such that no crystals are generated, the reflectivity of ultraviolet rays will not be reduced. In addition, if Si is contained, the mechanical strength of the aluminum foil can be improved by solid solution strengthening, so that a very thin foil can be easily rolled. When the content of Si is less than 0.001% by mass, the above-mentioned effect cannot be fully obtained. If the content of Si is higher than 0.3% by mass, coarse crystals are likely to occur, not only reducing the reflectivity, but also impairing the above-mentioned grain refinement effect, and the strength and processability also tend to be reduced.
[0060] It is more preferred that the content of magnesium (Mg) in the aluminum foil 1 is 3% by mass or less. Mg has the highest solid solubility in Al, which is as high as 18% by mass, and the occurrence of crystallized matter is extremely small, so the mechanical strength of the aluminum foil 1 can be improved without greatly affecting the reflective properties of the surface (first surface 1A) of the aluminum foil 1. However, if the content of Mg is higher than 3% by mass, the mechanical strength of the aluminum foil 1 is too high, so the rollability of the aluminum foil 1 tends to decrease. In order to make the aluminum foil 1 have both preferred reflective properties and mechanical strength, it is more preferred that the content of Mg is 2% by mass or less.
[0061] The aluminum foil 1 may contain elements such as copper (Cu), zinc (Zn), titanium (Ti), vanadium (V), nickel (Ni), chromium (Cr), zirconium (Zr), boron (B), calcium (Ga), and bismuth (Bi) in an amount that does not affect the above-mentioned characteristics and effects.
[0062] The composition of the aluminum foil 1 can be measured by inductively coupled plasma atomic emission spectrometry. Examples of the measuring apparatus include iCAP6500DUO manufactured by Thermo Fisher Scientific and ICPS-8100 manufactured by Shimadzu Corporation.
[0063] The aluminum foil 1 has a thickness of 500 μm or less. The aluminum foil 1 is literally a "foil" and is lightweight compared to aluminum plates having a thickness of more than 500 μm, has various advantages such as good formability, shape conformability when attached to curved objects, high flexibility, and low environmental impact.
[0064] The thickness of the aluminum foil 1 is preferably 4 μm or more and 300 μm or less. If the thickness of the aluminum foil 1 is less than 4 μm, the mechanical strength of the aluminum foil cannot be maintained, and wrinkles may occur on the surface of the aluminum foil due to the processing during manufacturing. If the thickness of the aluminum foil 1 is higher than 300 μm, not only the weight of the aluminum foil increases, but also the processing such as molding is restricted and is not preferred. More preferably, the thickness of the aluminum foil 1 is 6 μm or more and 250 μm or less. In order to make the thickness of the aluminum foil 1 within the above range, casting and rolling can be performed in accordance with the general manufacturing method of aluminum foil.
[0065] <Method for producing aluminum foil>
[0066] The manufacturing method of aluminum foil 1 comprises a first step of preparing aluminum foil, and a second step of forming a concave-convex surface on at least a portion of the surface of the prepared aluminum foil. In the first step, an aluminum foil containing Al and inevitable impurities is prepared. In the second step, at least one of the treatment methods for forming the above-mentioned concave-convex surface is implemented on at least a portion of the surface of the prepared aluminum foil. The treatment conditions at this time are set as follows: the area ratio of the second phase particles existing in a predetermined area of the concave-convex surface is less than 0.10%, the arithmetic mean curvature Spc (1 / mm) of the convex part of the concave shape is greater than 3700 and less than 10000, and the vertex density (1 / mm 2 ) is greater than 1,600,000 and less than 4,500,000.
[0067] In the second step, as long as the area ratio of the second phase particles existing in the predetermined area of the concavo-convex surface is 0.10% or less, the arithmetic mean curvature Spc (1 / mm) of the convex portion of the concavo-convex shape is 3700 or more and 10000 or less, and the vertex density (1 / mm) of the concave portion of the concave shape is 2 ) is 1600000 or more and 4500000 or less, then any treatment may be performed, and as an example, an immersion treatment in an alkaline aqueous solution may be cited. Below, as an example of a method for manufacturing the aluminum foil 1, a method for manufacturing the aluminum foil 1 having a second step of forming the above-mentioned concavoconvex surface using an alkaline aqueous solution is described.
[0068] In the first step, an aluminum foil containing Al, 0.04 mass % to 0.11 mass % Fe, and 0.50 mass % to 1.20 mass % Mn is prepared.
[0069] First, an ingot having a composition adjusted therein is obtained to obtain an aluminum foil of the above composition. The method for manufacturing the ingot is not particularly limited, and may be, for example, semi-continuous casting, continuous casting, or mold casting. The ingot may also be subjected to a homogenization heat treatment. The homogenization heat treatment is performed, for example, by maintaining the ingot in a temperature range of 400° C. to 630° C. for 1 hour to 20 hours.
[0070] Second, the ingot is rolled to obtain an aluminum foil of a specified thickness. During rolling, for example, after the ingot is hot-rolled, the obtained hot-rolled material can also be cold-rolled. When a thin plate-shaped ingot is prepared by continuous casting, the ingot can also be cold-rolled without hot rolling. There are no special restrictions on the number of hot rolling and cold rolling. When multiple cold rollings are performed, intermediate annealing can also be performed between multiple cold rollings. The conditions of intermediate annealing can be within the range of general operating conditions. In addition, after rolling (after the final cold rolling when multiple rollings are performed), a final annealing can also be performed. The conditions for the final annealing are, for example, an annealing temperature of more than 250°C and less than 450°C, and an annealing time of more than 1 hour and less than 30 hours.
[0071] In the second step, at least a portion of the surface of the aluminum foil prepared in the first step is exposed to an alkaline aqueous solution, so that concave-shaped concave-convex surfaces are formed in the portion. For example, the aluminum foil with only the area on the surface where the concave-convex surface is to be formed is exposed is immersed in an alkaline aqueous solution. In this step, any alkaline aqueous solution can be used, but a sodium hydroxide aqueous solution is preferred.
[0072] The concentration and temperature of the alkaline aqueous solution, as well as the treatment time and other conditions can be appropriately selected. The concentration of the alkaline aqueous solution is, for example, 0.1 mass % or more and 30 mass % or less. When the alkaline aqueous solution is a sodium hydroxide aqueous solution, the concentration of the sodium hydroxide aqueous solution is, for example, 0.1 mass % or more and 30 mass % or less. The temperature of the alkaline aqueous solution is, for example, room temperature. The treatment time is, for example, 1 minute or more and 60 minutes or less.
[0073] In the second step, it is preferred that at least a portion of the surface of the aluminum foil is exposed to an alkaline aqueous solution and then subjected to a treatment for removing the black stain. As a treatment for removing the black stain, for example, a treatment for removing the black stain using an acid or alkali other than acid washing or alkali washing can be cited. In addition, the black stain can also be removed by a physical treatment such as drum grinding or electrolytic grinding.
[0074] <Effects, etc.>
[0075] The aluminum foil 1 of the present embodiment has a concave-convex surface on which concave-convex portions of a concave shape are formed, the area ratio of the second phase particles existing in a predetermined area of the concave-convex surface is 0.10% or less, the arithmetic mean curvature Spc (1 / mm) of the convex portions of the concave shape is 3700 or more and 10000 or less, and the vertex density (1 / mm 2 ) is greater than 1,600,000 and less than 4,500,000.
[0076] The inventors of the present invention have confirmed that, in the aluminum foil 1 having such an uneven surface, although the total reflectivity when ultraviolet rays are irradiated to the uneven surface is 80% or more, the regular reflectivity is 4% or less. According to such an aluminum foil 1, the intensity of diffusely reflected ultraviolet rays is significantly higher than the intensity of regular reflected ultraviolet rays, so it is suitable for a reflector used for uniformly sterilizing a space to be sterilized.
[0077] The aluminum foil 1 preferably contains aluminum, 0.04 mass % to 0.11 mass % iron, and 0.50 mass % to 1.20 mass % manganese. The present inventors have confirmed that the above-mentioned uneven surface can be easily formed in such an aluminum foil 1 by exposing the aluminum foil 1 to an alkaline aqueous solution.
[0078] The thickness of the aluminum foil 1 is preferably 4 μm or more and 300 μm or less. Such an aluminum foil 1 also has high processability as described above.
[0079] The present inventors have confirmed that in the aluminum foil 1 , the arithmetic mean roughness (Ra) of the concavo-convex surface is larger than 20 nm.
[0080] The manufacturing method of the aluminum foil 1 of the present embodiment comprises the following steps: a step of preparing an aluminum foil containing aluminum, 0.04 mass % or more and 0.11 mass % or less of iron, and 0.50 mass % or more and 1.20 mass % or less of manganese; and a step of exposing at least a portion of the surface of the aluminum foil to an aqueous sodium hydroxide solution to form concave-shaped projections and depressions on at least a portion of the surface.
[0081] The present inventors have confirmed that the aluminum foil 1 of the present embodiment can be produced by such a production method.
[0082] <Properties of Aluminum Foil 1 Regarding Visible Light>
[0083] Furthermore, the present inventors have found that the aluminum foil 1 has suitable properties not only as a reflector for uniformly sterilizing a space to be sterilized, but also as a packaging material for packaging food, medicine, and the like.
[0084] In the past, when aluminum foil was used as a packaging material for packaging food or medicine, the area of the aluminum foil where the pattern and barcode of the packaging material were printed was usually whitened, and the pattern and barcode were printed on it. Generally speaking, aluminum foil also shows high reflectivity in the visible light region, but since most of the reflected light is regular reflection light, the color of the aluminum foil is silver. If the pattern and barcode of the packaging material are directly printed on the surface of the aluminum foil, the silver color of the aluminum foil becomes the bottom layer, which causes problems such as inaccurate color expression and difficulty in reading the barcode.
[0085] As methods for whitening aluminum materials, there are known methods of printing a white base layer on the surface of an aluminum foil, or a method of forming an anodized film. Regarding the latter method, for example, in Japanese Patent Gazette No. 2017-122267 (Patent Document 2), an aluminum material having an anodized film is proposed. However, in the aluminum material described in Patent Document 2, because there is an anodized film on the surface of the aluminum substrate, when the aluminum foil is subjected to heat of more than 100°C to be laminated with a different material, or sealed, or the contents are sterilized, the anodized film will rupture due to the different thermal expansion coefficients of the aluminum substrate and the anodized film. In addition, if the aluminum material is used for deep drawing, the hard and brittle anodized film will rupture.
[0086] The inventors of the present invention have discovered that, according to the aluminum foil 1 of the present embodiment described above, a white base layer and an anodized film are not required, and in the aluminum foil 1 alone, most of the reflected light is a diffuse reflection component, and the intensity of this diffuse reflection component is uniform regardless of the reflection angle. As a result, when visible light enters the aluminum foil 1, the surface appears white. In addition, its whiteness is so high that the above-mentioned problems regarding the accurate color display and barcode reading that occur in aluminum foil that has not been whitened do not occur.
[0087] Next, the high whiteness of the aluminum foil 1 will be described.
[0088] The inventors of the present invention have confirmed that, regarding the L* value of the first side 1A of the aluminum foil 1, the 15° reflectance value is greater than 140, the 45° reflectance value is greater than 70, and the 110° reflectance value is greater than 30, and that even when the pattern of the packaging material and the barcode are directly printed on the surface of the aluminum foil, the occurrence of problems such as the inability to display accurate colors or difficulty in reading the barcode can be suppressed on the surface of the aluminum foil 1.
[0089] The L* value of the first surface 1A of the aluminum foil 1 is measured using a colorimeter according to the method of ASTM D2244, E308, E1164, and E2194. Specifically, visible light is incident on the first surface 1A of the aluminum foil 1 at an incident angle of 45°, and the corresponding regular reflected light is measured using a colorimeter to measure the brightness L* value of each reflected light that deviates from the incident light side by 15°, 45°, and 110°.
[0090] The present inventors have confirmed that when the arithmetic mean curvature Spc (unit: 1 / mm) of the above-mentioned convex portion of the dimple shape of the first surface 1A of the aluminum foil 1 is greater than or equal to 3700 and less than or equal to 10000, the L* value, which is an indicator of the degree of whiteness under visible light, has a 15° reflectance value of greater than or equal to 140, a 45° reflectance value of greater than or equal to 70, and a 110° reflectance value of greater than or equal to 30.
[0091] It was also confirmed that when the arithmetic mean curvature Spc (unit: 1 / mm) of the convex portions of the dimple shape of the first surface 1A of the aluminum foil 1 was less than 3700 or greater than 10000, the L* value at each angle was low.
[0092] If the arithmetic mean curvature Spc (unit: 1 / mm) of the dimple-shaped convex portion is less than 3700, the angle range of diffuse reflection of visible light incident on the first surface 1A becomes narrower, so it is considered that the intensity of the regular reflection component is not sufficiently reduced and the intensity of the diffuse reflection component is not high enough.
[0093] If the arithmetic mean curvature Spc (unit: 1 / mm) of the above-mentioned convex portion of the concave shape of the first surface 1A of the aluminum foil 1 is greater than 10000, the angle range of diffuse reflection of visible light incident on the first surface 1A is too wide, and a part of the visible light diffusely reflected on the wall surface of the convex portion or concave portion of the concave shape is diffusely reflected again on the opposite wall surface, resulting in an increase in the amount of visible light reflected multiple times in the first surface 1A and a decrease in the amount of visible light emitted to the outside. Therefore, it can be considered that the L* value is reduced.
[0094] The present inventors have confirmed that in the aluminum foil 1, if the vertex density (unit: 1 / mm 2 ) is 1,600,000 or more and 4,500,000 or less, then with respect to the L* value which is an indicator of the degree of whiteness under visible light, the 15° reflectance value is 140 or more, the 45° reflectance value is 70 or more, and the 110° reflectance value is 30 or more.
[0095] The present inventors have confirmed that in the aluminum foil 1, if the vertex density (unit: 1 / mm 2 ) is less than 1510000, then regarding the L* value, the 15° reflectance value is less than 140, the 45° reflectance value is less than 70, and the 110° reflectance value is less than 30. It can be considered that if the vertex density (unit: 1 / mm 2 ) is less than 1510000, the number of dimples is small, so the diffuse reflection component becomes less, or the planar size of each dimple is large, so the angle range of diffuse reflection of visible light becomes narrower.
[0096] The present inventors have confirmed that in the aluminum foil 1, if the vertex density (unit: 1 / mm 2 ) is greater than 4650000, the L* values at 15° and 45° angles are low. The present inventors believe that the reason is that if the vertex density (unit: 1 / mm 2 ) is greater than 4650000, the planar size of each dimple is too small, and a part of the visible light diffusely reflected on the wall of the convex or concave part of the dimple shape is diffusely reflected again on the opposite wall, thereby increasing the amount of visible light reflected multiple times within the first surface 1A and reducing the amount of visible light emitted to the outside.
[0097] The reflectivity of visible light incident on the surface of the second phase particles present on the above-mentioned concavo-convex surface of the aluminum foil 1 is lower than the reflectivity of electromagnetic waves incident on the above-mentioned concavo-convex surface of the aluminum foil 1 itself. The present inventors have confirmed that if the area ratio of the second phase particles present in the predetermined region of the above-mentioned concavo-convex surface of the aluminum foil 1 is 0.10% or less, the 15° reflectance value is 140 or more, the 45° reflectance value is 70 or more, and the 110° reflectance value is 30 or more with respect to the L* value as an index of the degree of whiteness under visible light. In addition, the present inventors have confirmed that even if the area ratio of the second phase particles present in the predetermined region of the above-mentioned concavo-convex surface of the aluminum foil 1 is 0.02% or more, the 15° reflectance value is still 140 or more, the 45° reflectance value is still 70 or more, and the 110° reflectance value is still 30 or more with respect to the L* value as an index of the degree of whiteness under visible light.
[0098] On the other hand, the inventors of the present invention have confirmed that when the area ratio of the second phase particles present in the predetermined area of the above-mentioned concave-convex surface of the aluminum foil 1 is 1.97% or more, the L* value, which is an indicator of the degree of whiteness under visible light, is reduced to less than 70 at 45° reflectance and less than 30 at 110° reflectance.
[0099] Regarding the composition of the aluminum foil 1, when the Fe content is more than 0.11 mass %, after the surface of the aluminum foil 1 is exposed to an alkaline aqueous solution to form the above-mentioned uneven surface, the area ratio of the second phase particles existing (remaining) on the above-mentioned uneven surface is much higher than 0.10%, and regarding the L* value serving as an indicator of the degree of whiteness under visible light, the 45° reflectance value may be reduced to less than 70, and the 110° reflectance value may be reduced to less than 30.
[0100] When the Mn content is less than 0.50 mass %, after the surface of the aluminum foil 1 is exposed to an alkaline aqueous solution to form the above-mentioned concavo-convex surface, second phase particles with a small amount of Mn or no Mn remain on the above-mentioned concavo-convex surface, and the area ratio of the second phase particles is higher than 0.10%. Regarding the L* value serving as an indicator of the degree of whiteness under visible light, it is possible that the 45° reflectance value is reduced to less than 70, and the 110° reflectance value is reduced to less than 30.
[0101] When the Mn content is more than 1.20 mass %, as described above, the arithmetic mean curvature Spc (unit: 1 / mm) of the convex portion of the dimple shape is greater than 10000, and the vertex density (unit: 1 / mm) of the concave portion of the dimple shape is 2 ) is greater than 4500000, and regarding the L* value, which is an indicator of the degree of whiteness under visible light, it is possible that the 45° reflectance value is reduced to less than 70, and the 110° reflectance value is reduced to less than 30.
[0102] In addition, it was confirmed that the L* value, which is an index of whiteness under visible light, was 140 or more at 15°, 70 or more at 45°, and 30 or more at 110°. Such aluminum foil 1 can be used as an aluminum foil having a white surface without having a white printing on the base layer or an anodic oxide film.
[0103] As described above, the first surface 1A of the aluminum foil 1 has high whiteness alone. Therefore, the aluminum foil 1 does not require other laminates or anodized films, and thus can reduce environmental burden compared to conventional aluminum materials that are whitened by other laminates or anodized films.
[0104] Example
[0105] Next, aluminum foils of Examples and Comparative Examples of the present embodiment were prepared, and their total reflectance and regular reflectance were evaluated.
[0106] <Evaluation samples>
[0107] Aluminum ingots having different compositions were used to produce aluminum foils of Examples 1 to 6 and Comparative Examples 1 to 14 shown in Table 1 by the following production process. Comparative Example 14 is the aluminum foil described in Patent Document 1.
[0108]
Table 1
[0109]
[0110] First, after the molten aluminum adjusted to a specified composition is cast to obtain an ingot, the ingot is subjected to a homogenization heat treatment at a specified temperature and time. Thereafter, the ingot is hot rolled to obtain a hot-rolled material with a thickness of about 6.5 mm. The hot-rolled material is subjected to multiple cold rollings. During the multiple cold rollings, intermediate annealing is performed. In this way, aluminum foil having a thickness (original thickness) shown in Table 2 can be produced.
[0111] Next, the aluminum foils of Examples 1 to 6, Comparative Examples 1 to 9, and 11 to 14 were subjected to alkali treatment or acid treatment. The aluminum foils of Examples 1 to 6 and Comparative Examples 1 to 9 and 12 were immersed in a 1% sodium hydroxide aqueous solution for the time shown in Table 2. The aluminum foils of Comparative Examples 11 and 13 were immersed in an aqueous solution containing 8% hydrochloric acid and 4% aluminum chloride for the time shown in Table 2. Comparative Example 14 was immersed in a 1% sodium hydroxide aqueous solution for the time shown in Table 2. For the aluminum foil of Comparative Example 10, neither the above-mentioned alkali treatment nor the above-mentioned acid treatment was implemented. In addition, in order to remove black stains, the aluminum foils of Examples 1 to 6 and Comparative Examples 1 to 14 were immersed in a 5% nitric acid aqueous solution for 10 seconds, and then washed and dried. In this way, aluminum foils of Examples 1 to 6 and Comparative Examples 1 to 14 having the thickness (thickness after treatment) shown in Table 2 were produced. In addition, the liquid temperature of each of the above-mentioned aqueous solutions was 35°C. The thickness of the aluminum foils of Examples 1 to 6 and Comparative Examples 1 to 14 after treatment was measured using a digital micrometer MDC-MXIP65 manufactured by Mitutoyo Corporation.
[0112]
Table 2
[0113]
[0114] <Measurement of the arithmetic mean curvature Spc of the convex portions and the vertex density of the concave portions of the dimple shape>
[0115] For the aluminum foils of Examples 1 to 6 and Comparative Examples 1 to 14, respectively, the arithmetic mean curvature Spc of the above-mentioned convex parts of the dimple shape on the surface of the object and the vertex density of the above-mentioned concave parts were measured. Specifically, the concave and convex surfaces of each aluminum foil were observed using a laser microscope VK-X3000 manufactured by Keyence Corporation, and laser confocal shape measurement was performed in a rectangular field of view of 95.257μm×71.419μm. For the purpose of removing waviness, the surface shape correction was performed on the obtained three-dimensional shape data with a cutoff value of 0.1mm, and then a high cutting level correction was performed with a cut level of 50 for the purpose of removing the reflected noise component of the laser. For the above-mentioned corrected three-dimensional shape data, a reference plane was set as a plane representing the average of the concave and convex.
[0116] Based on the corrected three-dimensional shape data, the arithmetic mean curvature Spc (unit: 1 / mm) of the peak point specified in the International Organization for Standardization standard ISO25178 is measured using a multi-file analysis application program attached to the microscope.
[0117] In addition, the corrected three-dimensional shape data is inverted in the height direction relative to the reference plane, and the vertex density Spd (unit: 1 / mm) of the mountain specified in the International Organization for Standardization standard ISO25178 is measured by the multi-file analysis application based on the inverted data. 2). In other words, the vertex density of the above-mentioned concave portion of the dimple shape is measured as the peak point density of the inverted data.
[0118] <Measurement of the area ratio of the second phase particles>
[0119] For each of the aluminum foils of Examples 1 to 6 and Comparative Examples 1 to 14, the area ratio of the second phase particles on the surface of the object was measured. Specifically, JSM-7200F manufactured by JEOL Ltd. was used to observe five randomly selected rectangular fields of view on the concave and convex surface of each aluminum foil. The rectangular field of view was 1188.49 μm 2 Rectangular field of view (39.59 μm × 30.02 μm).
[0120] The image processing software WinRoof2021 manufactured by Mitani Shoji Co., Ltd. performs binarization processing on the backscattered electron images of each rectangular field of view to extract the second phase particles. In the observation conditions of the backscattered electron image, the brightness, contrast and voltage and current values of the electron beam are set in such a way that the elements other than the second phase particles such as rolling stripes, oil pits and dimple shapes formed on the surface in the rectangular field of view image are included in the range of 0 or more and 70 to 130 or less by brightness extraction by table lookup conversion before binarization. The extraction implemented by the binarization processing is specifically carried out by the following method. First, in order to remove the elements other than the second phase particles such as rolling stripes, oil pits and dimple shapes in the obtained rectangular field of view image, a brightness extraction by table lookup conversion is performed. The brightness extraction is performed by limiting the upper limit value to 255 and adjusting the lower limit value between 70 and 130. Secondly, a single threshold value binarization processing is performed for multiple pixels extracted from the rectangular field of view image. The threshold value of the binarization processing is 1.0. The pixels finally extracted as described above are regarded as pixels of the second phase particles, the total area thereof is measured, and the total area is divided by the area of the entire field of view to measure the area ratio of the second phase particles.
[0121] <Measurement of total reflectance>
[0122] The total reflectance of the concave-convex surface was measured for the aluminum foils of Examples 1 to 6 and Comparative Examples 1 to 14, respectively. The total reflectance was measured using a UV-visible spectrophotometer V570 manufactured by JASCO Corporation, and a standard white plate for integrating spheres manufactured by Labsphere was used as a reference to measure the total reflectance in the integrating sphere in the wavelength range of 250nm to 2000nm. Based on the total reflectance measurement values obtained, the average value of ultraviolet light in the wavelength range of 250nm to 400nm was obtained. The total reflectance was measured in two directions, the rolling direction (MD) and the direction perpendicular to the rolling direction (TD), and the total reflectance was evaluated using the average value.
[0123] <Measurement of regular reflectance>
[0124] The regular reflectance of the concave and convex surfaces of the aluminum foils of Examples 1 to 6 and Comparative Examples 1 to 14 was measured respectively. The regular reflectance was measured using a UV-visible spectrophotometer V570 manufactured by JASCO Corporation. The aluminum-plated plane mirror attached to the device as a standard mirror was used as a reference to measure the regular reflectance of light incident at an incident angle of 5° in the wavelength range of 250nm to 2000nm. Based on the regular reflectance measurement values obtained, the average value of ultraviolet rays in the wavelength range of 250nm to 400nm was obtained. The reflectance was measured in two directions: the rolling direction (MD) and the direction perpendicular to the rolling direction (TD), and the total reflectance was evaluated using the average value.
[0125] <Measurement of Arithmetic Mean Roughness Ra>
[0126] The arithmetic mean roughness Ra of the concave and convex surfaces of the aluminum foils of Examples 1 to 6 and Comparative Examples 1 to 14 was measured respectively. The arithmetic mean roughness Ra was measured using a scanning probe microscope AFM5000II manufactured by Hitachi High-Technologies Co., Ltd., in a rectangular field of view of 80 μm × 80 μm, for the surface shape in the dynamic force mode (non-contact). For the obtained observation results, the surface was obtained by least squares approximation, and the inclination of the sample was corrected by automatic tilt correction of the fitted three-dimensional surface, and the surface roughness Ra was measured. The surface roughness Ra is a value calculated by three-dimensionally expanding the arithmetic mean roughness Ra defined in JIS B0601 (2001 edition) and ISO4287 (1997 edition) in a manner that can be applied to the entire observed surface.
[0127] <Measurement of L* value>
[0128] The L* values of the aluminum foils of Examples 1 to 6 and Comparative Examples 1 to 14 were measured by the methods according to ASTM D2244, E308, E1164, and E2194. Specifically, visible light was incident on the concave-convex surface of each aluminum foil at an incident angle of 45°, and the corresponding regular reflected light was measured using a colorimeter MACi manufactured by BYK to measure the lightness L* values of each reflected light deviated from the incident light side by 15°, 45°, and 110°.
[0129] Table 3 shows the measured values of the above parameters for each of the aluminum foils of Examples 1 to 6 and Comparative Examples 1 to 14. Table 4 shows the measured values of the L* value for each of the aluminum foils of Examples 1 to 6 and Comparative Examples 1 to 14.
[0130]
Table 3
[0131]
[0132]
Table 4
[0133]
[0134] As shown in Table 3, the aluminum foils of Examples 1 to 6 have a concave-convex surface with concave-convex shapes. In the aluminum foils of Examples 1 to 6, the arithmetic mean curvature Spc (unit: 1 / mm) of the convex portion of the concave-convex surface is 3700 or more and 10000 or less, and the vertex density (unit: 1 / mm) of the concave portion is 2 ) is greater than 1600000 and less than 4500000, and the area ratio of the second phase particles present on the concave-convex surface is less than 0.1%. In the aluminum foil of Examples 1 to 6, the total reflectivity of ultraviolet rays with a wavelength of 250 to 400 nm is greater than 80.0%, and the regular reflectivity is less than 4.0%. In other words, it was confirmed that in Examples 1 to 6, most of the ultraviolet rays reflected by the concave-convex surface were diffusely reflected on the concave-convex surface. Such an aluminum foil is suitable for use as a reflective plate for uniformly sterilizing a space to be sterilized. In addition, as shown in Table 4, it was confirmed that in the aluminum foil of Examples 1 to 6, regarding the L* value of the concave-convex surface, the 15° reflectivity is greater than 140, the 45° reflectivity is greater than 70, and the 110° reflectivity is greater than 30. Such an aluminum foil is suitable for packaging materials for food and medicines.
[0135] The aluminum foils of Examples 1 to 6 contain 0.04 mass % to 0.11 mass % Fe and 0.50 mass % to 1.20 mass % Mn. The aluminum foils of Examples 1 to 6 were immersed in an aqueous sodium hydroxide solution as an alkaline aqueous solution to form the above-mentioned concavoconvex surface.
[0136] On the other hand, although the aluminum foils of Comparative Examples 1 to 9 and 12 have a concave-convex surface with concave-convex shapes, at least any one of the arithmetic mean curvature Spc of the convex part of the concave part, the vertex density of the concave part, and the area ratio of the second phase particles existing on the concave-convex surface does not satisfy the above-mentioned numerical range. Concave-convex shapes are not formed on the aluminum foils of Comparative Examples 10, 11, 13, and 14. The aluminum foils of Comparative Examples 1 to 14 have a total reflectivity of ultraviolet rays with a wavelength of 250 to 400 nm that does not reach 80.0%, or a regular reflectivity that is higher than 4.0%. In addition, in the aluminum foils of Comparative Examples 1 to 14, regarding the L* value of the concave-convex surface, the 15° reflectivity is less than 140, or the 45° reflectivity is less than 70, or the 110° reflectivity is less than 30.
[0137] The aluminum foils of Comparative Examples 1, 5, 7, and 8 have a regular reflectance of more than 4% because the arithmetic mean curvature Spc of the convex part is less than 3700. The aluminum foil of Comparative Example 5 has a regular reflectance of more than 4% because the arithmetic mean curvature Spc (unit: 1 / mm) of the convex part of the concavo-convex surface is less than 3700 and the vertex density (unit: 1 / mm 2) is less than 1600000, so not only the regular reflectivity is higher than 4%, but also the total reflectivity of ultraviolet rays does not reach 80%. The aluminum foil of Comparative Examples 7 and 8 has an arithmetic mean curvature Spc (unit: 1 / mm) of the convex part of the concave-convex surface less than 3700, and the area ratio of the second phase particles is greater than 0.10%. Therefore, not only the regular reflectivity is higher than 4%, but also the total reflectivity of ultraviolet rays does not reach 80%. The aluminum foil of Comparative Example 8 has an arithmetic mean curvature Spc (unit: 1 / mm) of the convex part of the concave-convex surface less than 3700, and the vertex density (unit: 1 / mm 2 ) is less than 1600000, and the area ratio of the second phase particles is greater than 0.10%, so the vertex density of the concave part (unit: 1 / mm 2 ) is 1600000 or more, the regular reflectance is higher than that of Comparative Example 7.
[0138] The aluminum foils of Comparative Examples 2 to 4, 6, and 9 have an arithmetic mean curvature Spc (unit: 1 / mm) of the convex portions of the concavo-convex surface of 3700 or more and 10000 or less, but an apex density of the concave portions (unit: 1 / mm 2 ) is greater than 1,600,000 and less than 4,500,000, but the area ratio of the second phase particles existing on the concave and convex surface is greater than 0.1%, so the total reflectance does not reach 80%.
[0139] The aluminum foil of Comparative Example 11 has a total reflectance of less than 80.0% and a regular reflectance of more than 4.0% because the arithmetic mean curvature Spc (unit: 1 / mm) of the convex portion is greater than 10,000 and the area ratio of the second phase particles existing (remaining) on the concave-convex surface is greater than 0.10%. The aluminum foil of Comparative Example 12 has a total reflectance of less than 80.0% and a regular reflectance of more than 4.0% because the arithmetic mean curvature Spc (unit: 1 / mm) of the convex portion of the concave-convex surface is greater than 10,000 and the vertex density (unit: 1 / mm 2 ) is greater than 4500000, so the total reflectivity of ultraviolet rays does not reach 80%. The aluminum foil of Comparative Example 13 has an arithmetic mean curvature Spc (unit: 1 / mm) of the convex part greater than 10000 and a vertex density (unit: 1 / mm 2 ) is greater than 4500000, and the area ratio of the second phase particles existing (remaining) on the above-mentioned concave and convex surfaces is higher than 0.10%, so the total reflectance does not reach 80.0%, and the regular reflectance is higher than 4.0%.
[0140] In particular, the aluminum foil of Comparative Example 1 has an Fe content of less than 0.04 mass %. It is believed that when the aluminum foil having an Fe content of less than 0.04 mass % is exposed to an alkaline aqueous solution, the dissolution proceeds slowly, the unevenness of the concave and convex surface caused by the dissolution increases, and the arithmetic mean curvature Spc of the convex portion is less than 3700.
[0141] In the aluminum foil of Comparative Example 5, the Fe content is less than 0.04 mass % and the Mn content is less than 0.50 mass %. In the aluminum foil of Comparative Example 8, the Fe content is more than 0.11 mass % and the Mn content is less than 0.50 mass %. It is considered that when the aluminum foil with a Mn content of less than 0.50 mass % is exposed to an alkaline aqueous solution, the second phase particles that do not contain Mn are likely to remain on the surface of the aluminum foil, and the area ratio of the second phase particles existing (remaining) on the above-mentioned concave-convex surface is higher than 0.10%.
[0142] The aluminum foils of Comparative Examples 2 to 4 and 6 to 9 have an Fe content of more than 0.11 mass %. It is considered that when the aluminum foil having an Fe content of more than 0.11 mass % is exposed to an alkaline aqueous solution, the area ratio of the second phase particles existing (remaining) on the concavoconvex surface is significantly higher than 0.10%.
[0143] The aluminum foils of Comparative Examples 11 and 13 have an Fe content of more than 0.11% by mass and a Mn content of less than 0.50% by mass. It is believed that after the aluminum foils having an Fe content of more than 0.11% by mass and a Mn content of less than 0.50% by mass are exposed to an acidic aqueous solution, the area ratio of the second phase particles existing (remaining) on the concavo-convex surface is significantly higher than 0.10%.
[0144] In the aluminum foil of Comparative Example 12, the Mn content is more than 1.20 mass %. It is considered that when the aluminum foil having a Mn content of more than 1.20 mass % is exposed to an alkaline aqueous solution, a large amount of fine Al-Fe-Mn-based crystals are removed from the surface, and fine dimples are densely formed, so that the arithmetic mean curvature Spc (unit: 1 / mm) of the above-mentioned convex portion of the dimple shape is greater than 10000, and the vertex density (unit: 1 / mm) of the above-mentioned concave portion of the dimple shape is greater than 10000. 2 ) is greater than 4500000.
[0145] The aluminum foils of Comparative Examples 10 and 14 do not have a concave-convex surface with concave-convex shapes. The aluminum foil of Comparative Example 10 has a smaller arithmetic mean curvature Spc of the convex parts and a higher regular reflectivity than the aluminum foil of Comparative Example 1. The aluminum foil of Comparative Example 14 has a smaller arithmetic mean curvature Spc of the convex parts and a higher regular reflectivity than the aluminum foil of Comparative Example 10.
[0146] From the above results, it can be confirmed that the arithmetic mean curvature Spc (unit: 1 / mm) of the convex part of the concavo-convex surface is 3700 or more and 10000 or less, and the vertex density (unit: 1 / mm) of the concavo-convex part is 2 ) is greater than 1600000 and less than 4500000, and the area ratio of the second phase particles existing on the concave-convex surface is less than 0.1%, the total reflectivity of the concave-convex surface is greater than 80%, and the regular reflectivity of the concave-convex surface is less than 4%.
[0147] Description of Reference Numerals
[0148] 1 Aluminum foil, 1A first side, 1B second side.
Claims
1. An aluminum foil having a concavoconvex surface on which concavoconvexities in a dimple shape are formed, The area ratio of the second phase particles existing in the predetermined region of the concavo-convex surface is 0.10% or less, The arithmetic mean curvature Spc of the convex portion of the dimple shape is greater than or equal to 3700 and less than or equal to 10000, and the unit of the arithmetic mean curvature Spc is 1 / mm. The vertex density of the dimple-shaped concave portion is greater than or equal to 1,600,000 and less than or equal to 4,500,000, and the unit of the vertex density is 1 / mm 2 .
2. The aluminum foil according to claim 1, wherein The aluminum foil contains: aluminum; 0.04 mass % to 0.11 mass % iron; 0.50 mass % or more and 1.20 mass % or less of manganese.
3. The aluminum foil according to claim 1, wherein The aluminum foil has a thickness of 4 μm or more and 300 μm or less.
4. The aluminum foil according to claim 1, wherein The arithmetic mean roughness Ra of the concave-convex surface is greater than 20 nm.
5. A method for producing an aluminum foil, wherein: The following processes are available: A step of preparing an aluminum foil containing aluminum, 0.04 mass % to 0.11 mass % iron, and 0.50 mass % to 1.20 mass % manganese; A step of forming dimple-shaped irregularities on at least a portion of the surface of the aluminum foil by exposing at least a portion of the surface of the aluminum foil to an alkaline aqueous solution.
Citation Information
Patent Citations
White aluminum material and production method therefor
JP2017122267A
Aluminum foil for ultraviolet light reflecting materials and method for producing same
WO2017158989A1